Cultural Narratives in Indonesian Local Films: Resistance to Global Homogeneity Through Representations of Language and Identity - Abdul Majid Sutarya; Abdul Maskur (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2025)
Global cultural homogeneity, driven by the hegemony of considerable culture, challenges the diversity and identity of local cultures in an increasingly connected world. This research explores the role of Indonesian local films as a space where local culture can survive, transform, and interact with global culture. Using a cultural philosophy approach, this research examines three local films Tilik (2018), Uang Panai (2016), and Yowis Ben (2018)-as a medium that not only represents but also maintains cultural values through language, narrative and vital visual elements. These films invite us to reflect on the relationship between local identity and global cultural forces and how media can be a tool of resistance against cultural hegemony that reduces diversity. The results show that local films can be a vehicle to celebrate differences and introduce the richness of Indonesian culture while opening space for a more inclusive intercultural dialog. This research recommends strengthening local film production and distribution strategies and the need for more in-depth policy support to balance globalization and preserve local culture.